Murder in the park - Dams, Jeanne M. (Dams, Jeanne M. Oak Park Village mystery., 2022)
June, 1925. Elizabeth Fairchild lives a quiet life in genteel Oak Park Village, Illinois. There, she forms a close friendship with gentle Mr Anthony. But tragedy strikes when Mr Anthony is found stabbed to death in the alley behind his shop. Why would anyone murder a mild-mannered antiques dealer? Could it have something to do with the mysterious customer who bought a gold pocket watch from Mr Anthony on the day he died? When one of her father's oldest friends is accused of the crime, Elizabeth determines to expose the real killer. With gangsters moving into the neighbourhood from nearby Chicago, could Elizabeth be seriously out of her depth? -- adapted from jacket